THE FUNCTIONS OF THE STATE AND IMPROVEMENT OF PUBLIC ADMINISTRATION SYSTEM IN MODERN AGE IN THE REPUBLIC OF AZERBAIJAN - QARIBOV, Asaf; HUSEYN, Afaq (Studia Universitatis Babes-Bolyai Studia Europaea, 2017)
As the theories of industrial-type economy in the period of globalization are not able to explain a number of processes and phenomena of the new economic system and the emergence of new guidelines and priorities proses the problems tatesrevise their economic policies and careful choice of mechanisms for the implementation of its directions. In this article we will try to determine the priorities of global economic development and the challenges, state mechanisms and to resolve them.